Design of Object Detection Radar Robot Prototype using Passive Intra Red Sensor Based on Arduino Microcontroller - Djufri, Ilham; Subhan; Yakseb, Yanto (KH. A. Wahab Hasbullah University, 2023)
The research aims to design a radar robot prototype based on an Arduino microcontroller, using a Passive Infra-Red sensor and an ultrasonic sensor to identify objects within range. The objects detected are humans and RC aircraft. The RC aircraft is designed to be controlled remotely using a Flysky F16 remote control handheld radio transmitter and infrared lights installed so that ultrasonic sensors and PIR sensors can detect objects. A micro servo motor drives the radar robot. The method used is Prototype with the stages of Requirements Gathering, Prototype Design, Prototype Evaluation, System Coding, System Testing, System Evaluation, and System Implementation. The research result of the design is to detect humans and RC aircraft. In principle, the tool can read targets' movements (objects), namely humans and RC aircraft.